To solve this system of equations, we can substitute the second equation into the first equation:
2x + 3x + 2 = -4
5x = -6
x = -6/5
Now that we have the value of x, we can substitute it back into the second equation to solve for y:
y = 3(-6/5) + 2
y = -18/5 + 2
y = -18/5 + 10/5
y = -8/5
Therefore, the solution to the system of equations is (-6/5, -8/5). So, the correct answer from the list of options is (-6/5, -8/5).
Solve the system of equations and choose the correct answer from the list of options.
2x + Y = -4
Y = 3x + 2
(-8/5, -6/5)
(-6/5, -11/5)
(-11/5, -6/5)
(-6/5, -8/5)
1 answer